REGENERASI ALAMIAH BAMBU DI AREAL GARAPAN KELOMPOK TANI HUTAN KARYA MAKMUR II DALAM TAMAN HUTAN RAYA WAN ABDUL RACHMAN - Rahmadani, Bela Dwi (Fakultas Kehutanan Universitas Winaya Mukti, 2023)
The existence of bamboo in forest areas is very important because the strong root structure of rhizomes allows bamboo to bind soil and water properly, and this is no exception in Wan Abdul Rachman Grand Forest Park. Bamboo growth is closely related to the influence of environmental conditions where bamboo grows. Fertile soil affects the growth of bamboo because the nutrients for bamboo growth are met. The objectives of this research are to determine the regeneration rate of bamboo and the ecological conditions of each species of bamboo. This research was conducted in the area at the cultivated area of Karya Makmur II Forest Farmers Group in Wan Abdul Rachman Grand Forest Park on January 2023. The method used was the exploration method which is carried out by exploring areas that are often overgrown with bamboo. The results of the research were observed that 5 species of bamboo each had a youth percentage of 17.4% for betung bamboo, 24.3% for andong bamboo, 23.9% for mayan bamboo, 12.7% for tali bamboo, and 15.8% for black bamboo. The bamboo grows at an altitude of 150–304 m above sea level, slope of 25–60%, soil acidity of 5.0–6.5, air temperature of 27.6–29.7oC, and humidity of 60–85% and has a soil texture in the form of loamy loam, clay and loam. The conclusion of this reaserch is, although bamboo can grow in a humid or dry environment, however bamboo's regeneration rate is higher in a humid environment.